(untitled) - Codex Alimentarius Commission (Rome, Italy, 2007)
This volume includes Codex standards on milk, milk powders, condensed milks, creams, butter and all sorts of cheeses, and other related texts such as the Code of Hygienic Practice for Milk and Milk Products, published in this compact format to allow their wide use and understanding by governments, regulatory authorities, food industries and retailers, and consumers. This first edition includes all texts adopted by the Codex Alimentarius Commission up to 2007 (Editorial Reviews)
Keywords: Milk,Dairy products,Milk,Sữa,Sữa,Sản phẩm sữa; Standards,Standards,Quality,Tiêu chuẩn,Sữa - chất lượng,tiêu chuẩn